Ventilation and gas exchange in two turtles: Podocnemis unifilis and Phrynops geoffroanus (Testudines: Pleurodira) - Cordeiro, Tabata E. F. (2016)
Turtles (Testudines) have two major taxa, Pleurodira and Cryptodira. To date, only limited data are available regarding the respiratory physiology of pleurodirans. To begin to address this, we studied ventilation and gas exchange in Podocnemis unifilis and Phrynops geoffroanus. Breathing pattern in both species could be described as episodic with breathing episodes separated by large non-ventilatory periods. We measured duration of inspiration and expiration, breathing frequency, duration of the non-ventilatory period (time between episodes), tidal volume, and oxygen consumption when breathing normoxia, hypoxia and hypercarbia at 25 degrees C. In both species hypercarbia caused a greater increase in ventilation compared to hypoxia, increasing both breathing frequency and tidal volume. Minute ventilation and oxygen consumption in P. geoffroanus were the lowest described so far in testudines, indicating either extra-pulmonary gas exchange or a significantly lower metabolism. Oxidative costs of breathing, estimated using the regression method, was the highest described so far for any reptile. Further studies are necessary to better understand respiratory physiology in Phrynops and Podocnemis species. (C) 2014 Elsevier B.V. All rights reserved.